The Oldest Colchian Gold – Cultural Background and International Context - Kobalia, Nino (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2022)
The earliest gold items appeared in the territory of eastern Georgia during the 3rd millennium BC, in the so-called Early Barrows Culture; this continued until the Middle Bronze Age (mid-2nd millennium BC). After the Trialeti Great Barrows Culture period, almost no gold and silver items were found on the sites dating from the second half of the 2nd millennium to the beginning of the 1st millennium BC. Objects dating after this gap, during the 8th-6th centuries BC, have been discovered in various types of archaeological sites of Colchis. This paper aims to discuss the local and international cultural background based on which pre-classical Colchian goldsmithery was formed.